2017
DOI: 10.1016/j.jadohealth.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of State Competitive Food and Beverage Regulations on Childhood Overweight and Obesity

Abstract: Purpose Policy efforts for combating childhood obesity have sought stronger state policies for regulating competitive foods and beverages (CF&Bs) available in schools. However, the evidence linking state policies to children’s overall diet and body weight outcomes is limited and mixed, and experts have called for more rigorous studies that are able to address concerns about selection bias. The present study leverages a rare natural experiment where children in military families are “assigned” to different stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…The current follow-up evaluation conducted a decade after the introduction of a school food policy in WA public schools provides further evidence that such policies can be valued by key stakeholders and can make a positive difference to food provision in the school environment (9)(10)(11)(12)(13)(14)22) . Large majorities of respondents agreed that the policy has made the foods provided in schools healthier (85 %) and that it constitutes a valuable opportunity to teach children about healthy eating (90 %).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The current follow-up evaluation conducted a decade after the introduction of a school food policy in WA public schools provides further evidence that such policies can be valued by key stakeholders and can make a positive difference to food provision in the school environment (9)(10)(11)(12)(13)(14)22) . Large majorities of respondents agreed that the policy has made the foods provided in schools healthier (85 %) and that it constitutes a valuable opportunity to teach children about healthy eating (90 %).…”
Section: Discussionmentioning
confidence: 91%
“…An additional factor is likely to be the escalation in community concern about child obesity over the last decade (24) , which may have contributed to higher scores in the 2016 evaluation due to growing acceptance of the need for policy measures to address this issue. Previous research has found that school food policies can be associated with lower levels of child obesity (13,14) , highlighting the importance of such policies as a critical component of population-level child health strategies. Of note are the lower levels of policy compliance reported in the follow-up evaluation compared with the original evaluation (81 % v. 89 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What may matter for their effectiveness is the specific kinds of policies that states can reasonably implement with strong fidelity in local school settings. For instance, recent research on the impact of statewide policies that regulate foods and beverages in public schools-known as competitive food and beverage (CF&B) policies [29]showed that adolescents exposed to a range of CF&B policies, including regulations on vending machines and foods sold via school fundraisers, were strongly related to lowering the odds of being overweight or obese relative to having no policy at all [30]. Importantly, the number of policies mattered.…”
Section: Discussionmentioning
confidence: 99%
“…In this month's issue of the Journal of Adolescent Health, a new study by Datar and Nicosia [7] brings sharper focus to bear on how statewide policies can impact obesity. The study generates novel insights into how statewide policies that regulate foods and beverages in public schoolsdknown as competitive food and beverage (CF&B) policies [8]dhave impacted adolescents' obesity and obesity-related outcomes.…”
mentioning
confidence: 99%